Debelinska rast in odziv duglazije (Pseudotsuga menziesii (Mirb.) Franco) in smreke (Picea abies (L.) Karst.) na podnebje na produktivnem rastišču Pečovnika pri Celju - Levanič, Tom (Gozdarski vestnik, 2021)
We analysed the growth of Douglas fir (Pseudotsuga menziesii (Mirb.) Franco) and Norway spruce (Picea abies (L.) Karst.) at a productive site in Pečovnik near Celje. The analysed Douglas firs were slightly younger than spruces (67 vs 71 years) and grew slightly better (4.57 mm vs 3.26 mm per year). The climatic response of Douglas fir on the productive site was very pronounced. The radial increment was statistically significantly influenced by above-average temperatures in February and March and above-average precipitation in July. Compared to spruce, the climatic response of Douglas-fir is temporally stable and significantly more pronounced. Analysis of pointer years has shown that negative pointer years in Douglas-fir are always associated with very cold weather in February and March and positive years with above-average temperatures in the same two months. Summer precipitation has played a more important role in Douglas-fir only in the last three decades, but not before that. This suggests a potential lack of water in an otherwise very productive site that could lead to drought stress and poorer growth of Douglas-fir in the long term, given climate change trends.
Keywords: climate change; climate response; debelinski prirastek; dendrochronology; dendrokronologija; drought; duglazija; podnebne spremembe; radial increment; smreka; suša